Neuronal hyperactivity due to loss of inhibitory tone in APOE4 mice lacking Alzheimer's disease-like pathology. Issue 1 (December 2017) - Nuriel, Tal; Angulo, Sergio; Khan, Usman; Ashok, Archana; Chen, Qiuying; Figueroa, Helen; Emrani, Sheina; Liu, Li; Herman, Mathieu; Barrett, Geoffrey; Savage, Valerie; Buitrago, Luna; et al.
Abstract The ε4 allele of apolipoprotein E (APOE ) is the dominant genetic risk factor for late-onset Alzheimer's disease (AD). However, the reasonAPOE4 is associated with increased AD risk remains a source of debate. Neuronal hyperactivity is an early phenotype in both AD mouse models and in human AD, which may play a direct role in the pathogenesis of the disease. Here, we have identified anAPOE4 -associated hyperactivity phenotype in the brains of agedAPOE mice using four complimentary techniques—fMRI, in vitro electrophysiology, in vivo electrophysiology, and metabolomics—with the most prominent hyperactivity occurring in the entorhinal cortex. Further analysis revealed that this neuronal hyperactivity is driven by decreased background inhibition caused by reduced responsiveness of excitatory neurons to GABAergic inhibitory inputs. Given the observations of neuronal hyperactivity in prodromal AD, we propose that thisAPOE4 -driven hyperactivity may be a causative factor driving increased risk of AD amongAPOE4 carriers. The APOE4 allele is the leading risk factor for late-onset Alzheimer's disease, but how it might contribute to the disease is not clear. Here the authors show that a mouse expressing the human APOE4 allele displays hyperactivity in the entorhinal cortex due to a decreased inhibitory tone, which may in part explain accelerated Alzheimer's pathology in APOE4 carriers.